Start block kinetics: what the best do different than the rest - Willwacher, S.; Herrmann, V.; Heinrich, K.; Brüggemann, G. P. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to analyze the push - off forces of male and female sprinters from a wide range of performance levels, including the currently two fastest sprinters in the world. A force start block was used to measure the forces applied to the front and rear blocks. In total, 430 full effort starts of over 99 subjects were analyzed. World - class athletes did not leave the blocks with a higher center of mass velocity, but with a shorter block time. They were able to produce higher maximum forces and rates of force development. Maximum forces were more balanced between the front and rear leg. These results further highlight the importance of high force capacities for a successful sprint start. The more evenly distributed maximum forces of the front and rear leg of world - class athletes might be a technical feature that could help lower level athletes to improve their performance. Training success should be monitored using force measurements in the blocks.